Preventive Practices of Tuberculosis Patients in a Municipality of Chitwan District, Nepal - Bansal, Prerna; Khatiwada, Dipendra; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2019)
Background: Tuberculosis (TB) is one of the top 10 causes of death worldwide and sixth leading cause of death in Nepal. Preventing new infections of Mycobacterium tuberculosis is crucial to reduce TB burden and death. The source of infection is an open (sputum positive) case of pulmonary tuberculosis. Poor management of TB-related waste like disposal of sputum by patients has been reported as a risk factor for increasing susceptibility to active TB infection. The present study was undertaken to assess preventive measures practiced by TB patients. Methods: A cross-sectional study was conducted among 82 tuberculosis patients who visited the five different DOTs centres of Bharatpur Municipality of Chitwan district, Nepal during December 2016 to February 2017. To find the association between variables, chi-square test was used. P-value less than 0.05 were considered as statistically significant. Results: The Mean ± SD of age of patients was 37.02±18.90 years. 67.10% of the patients received health education on preventive measures. 59.8% of the respondents had good practice on prevention measures of TB. Only 3.70% used burning method for the sputum disposal after diagnosis of TB. None of the respondents used boiling method for the disposal of sputum. Among all only 6% practiced safe method of sputum disposal. The statistically significant variables with health education were preventive measures like self isolation (ᵪ2 = 7.54, p = 0.006), covering face while coughing and sneezing (ᵪ2 = 4.113, p = 0.043) and keeping surrounding clean (ᵪ2= 7.880, p = 0.005). Conclusions: Patients and family members should be well educated on practicing different preventive measures by further strengthening the preventive measures strategy in the transmission of tuberculosis if we envisioned to end TB by 2035.